Securing Personal Data: Unveiling The Crucial Role Of Legal Education In Non-Fungible Token Sites - Silviani, Ninne Zahara; Abrar, Farhan Rabbani (Widya Yuridika, 2024)
With the rapid advancement of technology, the emergence of Non-Fungible Token (NFT) platforms has revolutionized digital buying and selling. However, this innovative platform has also given rise to a concerning issue: the unintentional trade of personal data instead of artwork. This problem poses a significant challenge in protecting individuals' personal information, especially when items like National Identity Card (KTP) photos are sold as NFT assets. This research aims to explore the critical importance of legal education in safeguarding personal data, thus preventing such transactions that may lead to self-harm. Employing a normative juridical method and a conceptual approach, this study extensively analyzes legal aspects and regulations related to personal data protection. The findings underscore the urgent need for legal education to effectively address personal data transactions on NFT sites within marketplace platforms. Despite the implementation of the Personal Data Protection Act (Law Number 27 of 2022), it is clear that the legislation alone is insufficient. Given the gravity of the issue, comprehensive public education initiatives involving various segments of society are crucial. Protecting personal data has become a matter of utmost concern for the government, the state, NFT platform users, and internet users at large. Individuals must adopt a vigilant and proactive approach in safeguarding their personal data. Legal education programs, including outreach activities conducted by governmental and non-governmental entities, along with the involvement of students and academics in community counseling, can effectively support this objective.